Impact of Microfinance on Poor Women : Lessons from North Gujarat - Patel, Ritesh; Patel, Mitesh; Patel, Nikunj (Prabandhan: Indian Journal of Management, 2018)
Today, microfinance is considered as one the important financial services in many countries. Microfinance is preferred to alleviate poverty. It empowers women and uplifts their standard of living. The present study was conducted to assess the impact of microfinance on poor women. This study was done on 384 poor women in North Gujarat who had the Below Poverty Line (BPL) Card. This study was carried out using correlation, regression, and factor analysis. From the factor analysis on 30 variables, four major factors emerged : (a) Enhancement in Quality of Food, Education, Shelter, and Health Services, (b) Enhancement in Monthly Income and Spending, (c) Enhancement in Decision Making Ability, and (d) Development of Personality. Correlation analysis revealed that data was fit for performing regression analysis. A regression analysis was run on the four factors derived from factor analysis, where the Enhancement in Monthly Income and Spending contributed the most ; whereas, Development of Personality contributed the least to the upgradation of social and economic status of women. Overall, the study has practical implications where the government and non government organizations (NGOs) can work on microfinance services and can reduce the level of poverty and uplift the living standard of poor people.